[RETRACTED] PEREMPUAN BEPERGIAN TANPA MAHRAM (Studi Kasus Dekrit Kerajaan Arab Saudi Nomor M/134 Tahun 2019) - Firqah Annajiyah Mansyuroh (Universitas Islam Negeri Imam Bonjol Padang, 2020)
[THIS ARTICLE HAS BEEN RETRACTED] This is based on the original author's report that the article was previously published in another journal. The article has been published in AL-IHKAM: Journal of Law and Social Institutions (Publisher The Islamic Law Researcher Association (APHI) collaboration with Faculty of Sharia IAIN Madura) Vol 14, No 2 (2019) DOI: http://dx.doi.org /10.19105/al-lhkam.v14i2.2785.This article has followed the procedures which apply in the journal management. The author has received the review results and improved the article according to the review.One of the requirements for submitting a paper to be published in this journal is that the author states explicitly that his/her work is original and has not appeared in other publications, and is not considered by other journals. Because of this, this article represents a severe misuse of the scientific publishing system. The scientific community has very strong views on this issue, and we apologize to the readers of the journal that this was not detected during the submission process.